2011
DOI: 10.1016/j.ymeth.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Applications of analytical ultracentrifugation to protein size-and-shape distribution and structure-and-function analyses

Abstract: The rebirth of modern analytical ultracentrifugation (AUC) began in 1990s. Since then many advanced AUC detectors have been developed that provide a vast range of versatile choices when characterizing the physical and chemical features of macromolecules. In addition, there have been remarkable advances in software that allow the analysis of AUC data using more sophisticated models, including quaternary structures, conformational changes, and biomolecular interactions. Here we report the application of AUC to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It is unable to confirm that our observation is a substrate-induced or substrate/product-induced dimerization. To solve this, a modified AUC technique, AEC [ 33 ], was utilized to detect the quaternary structure change in the absence and presence of substrate ( Fig 4 ). Here the enzyme solution was put into the small well of band-forming centerpiece and then flowed into the substrate-containing channel when the centrifugation began.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unable to confirm that our observation is a substrate-induced or substrate/product-induced dimerization. To solve this, a modified AUC technique, AEC [ 33 ], was utilized to detect the quaternary structure change in the absence and presence of substrate ( Fig 4 ). Here the enzyme solution was put into the small well of band-forming centerpiece and then flowed into the substrate-containing channel when the centrifugation began.…”
Section: Resultsmentioning
confidence: 99%
“…Thus it can be concluded that, like the SARS-CoV M pro R298A mutant [ 25 ], the presence of substrate is able to induce the dimerization of MERS-CoV M pro . In addition, although the K d values of wild-type SARS-CoV M pro without or with substrates show no significant difference ( Table 2 ), it was possible to detect substrate-induced dimerization at a protein concentration of 1 μM by AEC [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple scans at different time intervals were then fitted to a continuous c(s, f/f 0 ) distribution model using the SEDFIT program [14,[21][22][23]. The protein concentrations of 13 lM in 50 mM phosphate buffer at various concentrations of urea.…”
Section: Analytical Ultracentrifugation Analysismentioning
confidence: 99%
“…The absorbance at 230 or 280 nm was monitored in continuous mode with a time interval of 300 s and a step size of 0.003 cm. Multiple scans at different time intervals were then fitted to a continuous c(M) distribution model using SEDFIT 37 38 .…”
Section: Methodsmentioning
confidence: 99%